Innovative approaches in language learning. (Eurasian Journal of Philology Science and Education, 2022)
Various concept of innovational approaches of learning languages have been analyzed and their actual definition has been proposed in the article. The article is considered development not only practical knowledge of English, but also the ability to work with information, that is, the ability to think, communicative competence. The game method in teaching a foreign language, which are wide demand in society, and actively used by teachers in the practice of teaching foreign languages in higher education, in corporate learning and specialized courses continuing education. In addition, this article also provides a scientific review on exploring the characteristics of an integrated English Only Space language studio and the impact further development of language competencies among teachers and students. Interaction with people of different social and cultural backgrounds requires oral communication, understanding, and dialogue to interact effectively. Therefore, using the English Only Space (EOS) integrated language studio, it develops communicative competence, problem-solving skills, students’ critical thinking skills, information analysis and reasoning. English Only Space serves as a driver for active start-up research in the field of innovative education. So, about 182 students of the Multilingual Education Faculty of Kh. Dosmukhamedov Atyrau University took part in the research. Key words: innovation, approaches, linguistics, communication, EOS, language learnin